Estrategias lúdicas virtuales para estimular el desarrollo de habilidades numéricas en niños de Educación Inicial - Pico Espín, Johanna Elizabeth (2022)
Currently, virtual playful strategies are essential resources for fulfilling the teacher's responsibilities in the teaching-learning process and in the development of numerical skills of children in initial education, for this reason, the objective of the work was to potentiate the development of Numerical skills in children of Initial Education in the Darío Guevara Educational Unit with the use of virtual playful strategies. The methodology followed a mixed modality or approach, that is, it was qualitative and quantitative for the analysis of the factors that affect the application of the strategies, this was defined by the application of observations to the children in two moments and interviews with the teachers; which means that for the study of the variables a pre-test and a post-test were developed, based on the observation sheet addressed to the children. After the evaluation with the pretest, the intervention proceeded through the application of a guide, during the normal day of daily school activities, in an organized way, without interfering with their tasks. The results of the pretest revealed that children in general had problems in the development of numerical skills, which is why a Guide to virtual playful strategies was developed to stimulate the development of numerical skills in children of Early Childhood Education. The same, which was structured in five main blocks to facilitate the use of applications through a link, with the approach of different topics with activities of easy development, with applicable links on any device. After having applied the proposal, the post-test was developed that showed a significant improvement in the children in relation to their numerical skills. The proposal was validated by experts and users who qualified it as excellent and suggested its application in preschool children.